2023
DOI: 10.1111/csp2.12883
|View full text |Cite
|
Sign up to set email alerts
|

What drives local communities' attitudes toward the protected area? Insights from Bardia National Park, Nepal

Abstract: Understanding the local communities' attitudes toward protected areas (PAs) is critical to PA management planning. However, what socio‐economic and demographic factors drive their attitude remains poorly studied. We interviewed 135 residents in three villages in the buffer zone of Bardia National Park, Nepal, to assess their perceived benefits and costs of the PA. We found that perceived benefits are skewed toward wealthy and influential people, whereas costs associated with wildlife‐caused damage (i.e., crop … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
2
5
0
Order By: Relevance
“…Similarly study conducted by Ref. 29 , 30 indicated that the relationship between park and peoples were negative due to crop and livestock damage by wildlife, and restrictions imposed by the reserve authorities in collecting forest products. Moreover the pressure and conflict from conservation authorities, grazing fines, and benefits are for government.…”
Section: Discussionmentioning
confidence: 94%
“…Similarly study conducted by Ref. 29 , 30 indicated that the relationship between park and peoples were negative due to crop and livestock damage by wildlife, and restrictions imposed by the reserve authorities in collecting forest products. Moreover the pressure and conflict from conservation authorities, grazing fines, and benefits are for government.…”
Section: Discussionmentioning
confidence: 94%
“…Past studies conducted in Nepal's PAs have also concluded that local attitudes towards PAs have improved, especially in areas where local residents have directly or indirectly benefitted from the programmes conducted by a PA or the tourism that depends on it (Spiteri & Nepal 2008, Shahi et al 2023. Although the benefits generated from the PA itself are limited in order to substantially benefit a broader population, the BZP was intended to provide more benefits to local residents.…”
Section: Discussionmentioning
confidence: 99%
“…The level of respondent education was used as a control variable because education could impact how people perceive the value of PAs and affect perceptions of the relationship between people and PAs (Shahi et al 2023). This variable was measured using six levels of education (1 = no education at all, 2 = literate, 3 = some schooling, 4 = high school education, 5 = some college-level education, 6 = a college degree).…”
Section: Educationmentioning
confidence: 99%
See 2 more Smart Citations